On gas and hydraulic tightness of accelerating sections - Zhiglo, V.F. (Вопросы атомной науки и техники, 2021)
A technique for calculating the required impenetrability of brazing linac accelerating sections cooled by water and for control of their hydraulic tightness based on the total helium leakage rate is given. Three types of cooling systems: a water stream in tubes soldered on the outer surface of the sections, a water stream along the outer surface and along the internal cooling channels in sections are considered. It is shown that the contact of accelerating sections surface with cooling water requires increasing the tightness of their soldering at least by 66 times. As an example, requirements for hydraulic and air tightness of accelerating sections for the developed accelerator LU-10 NSC KIPT are given. Наведена методика розрахунку герметичності пайки прискорюючих секцій ЛПЕ, що охолоджуються водою, і оцінки герметичності за загальним натіканням гелію в прискорюючу секцію. Розглянуті три типи систем охолодження: потоком води в трубках, напаяних на зовнішній поверхності секцій, потоком води по зовнішній поверхні і по внутрішніх каналах охолодження секцій. Показано, що контакт поверхні прискорюючих секцій з охолоджувальною водою вимагає підвищення герметичності їх пайки, принаймні, в 66 разів. Як приклад наведені вимоги до герметичності прискорюючих секцій прискорювача ЛП-10, що розроблюється в ННЦ ХФТІ. Приведена методика расчета требуемой герметичности пайки ускоряющих секций ЛУЭ, охлаждаемых водой, и контроля их гидравлической герметичности по общему натеканию гелия. Рассмотрены три типа систем охлаждения: потоком воды в трубках, напаянных на наружной поверхности секций, потоком воды по наружной поверхности и по внутренним каналам охлаждения секций. Показано, что контакт поверхности ускоряющих секций с охлаждающей водой требует повышения герметичности их пайки, по крайней мере, в 66 раз. В качестве примера приведены требования к герметичности ускоряющих секций ускорителя ЛУ-10, разрабатываемого в ННЦ ХФТИ.